2004
DOI: 10.1111/j.1741-4520.2003.00002.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of the mouse exo utero development system in the study of developmental biology and teratology

Abstract: The mouse exo utero development system is useful for analyzing the roles of molecules or interactions between tissues in the histogenesis of organs after the mid-gestational period. In the article presented here, we review the mouse exo utero development system and its specific modifications depending on different purposes as well as its advantages over and limitations compared to other systems in the study of developmental biology and teratology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 31 publications
2
29
0
Order By: Relevance
“…After the operation, the fetuses together with the uterus were placed back in the abdominal cavity of the dam, and the incision on the abdominal muscle was sutured closed with 3-or 4-0 silk line; incision of the abdominal skin was closed by autosuture (MikRon 9 mm Autoclip Applier), and were allowed to develop exo utero till E18.5. As in our several previous studies (Hatta et al, 1994(Hatta et al, , 2002(Hatta et al, , 2004Habib et al, 2005Habib et al, , 2007Jahan et al, 2010), we observed that the exo utero surgery as described caused no general growth retardation, and neither the CRL, BW, nor the mandibular morphology of the E18.5 sham-operated fetuses were significantly different from those of the E18.5 in utero normal fetuses. Therefore, we here show only the results of sham-operated fetuses, and not those of in utero normal fetuses, as the control.…”
Section: Exo Utero Surgery Of Mouse Fetuses To Restrict Temporomandibsupporting
confidence: 84%
“…After the operation, the fetuses together with the uterus were placed back in the abdominal cavity of the dam, and the incision on the abdominal muscle was sutured closed with 3-or 4-0 silk line; incision of the abdominal skin was closed by autosuture (MikRon 9 mm Autoclip Applier), and were allowed to develop exo utero till E18.5. As in our several previous studies (Hatta et al, 1994(Hatta et al, , 2002(Hatta et al, , 2004Habib et al, 2005Habib et al, , 2007Jahan et al, 2010), we observed that the exo utero surgery as described caused no general growth retardation, and neither the CRL, BW, nor the mandibular morphology of the E18.5 sham-operated fetuses were significantly different from those of the E18.5 in utero normal fetuses. Therefore, we here show only the results of sham-operated fetuses, and not those of in utero normal fetuses, as the control.…”
Section: Exo Utero Surgery Of Mouse Fetuses To Restrict Temporomandibsupporting
confidence: 84%
“…At E15.5, exo utero surgery was performed basically as previously described . This experimental system allows researchers to manipulate or operate live embryos of mice or rats from mid‐ to late gestation and keep them alive in situ until the effects are analyzed at a desired time point either pre‐ or postnatally .…”
Section: Methodsmentioning
confidence: 99%
“…Using the exo utero system (Hatta et al 2004), we have established a method to apply ACTH to mouse embryos during the histogenetic period (Zhang et al 1998(Zhang et al , 1999. Systematic examination of these ACTHtreated embryos on the tissue and organs where MC2R and/or MC5R are expressed will provide information on the role of ACTH and MCRs in mouse embryogenesis.…”
Section: Brain and Spinal Cordmentioning
confidence: 99%
“…The authors further reported that MC2R mRNA was expressed in the fetal mouse testis by RT-PCR studies, and that incubation of fetal or neonatal testis with ACTH in vitro stimulated testosterone production. We previously showed that AtT20 cells, an ACTHsecreting tumor cell line, transplanted by exo utero manipulation (Hatta et al 2004) into mouse embryos on embryonic day (E) 14.5, elevated the plasma ACTH level and changed the morphology and steroidogenesis of the adrenal cortex at E18.5 (Zhang et al 1998). These findings suggest that ACTH and its receptors (mainly MC2R and MC5R) play roles in the mouse during mouse embryogenesis.…”
Section: Introductionmentioning
confidence: 98%